Pouvoir politique et économie mondiale : une esquisse théorique - BRETON, Gilles (Sociologie et sociétés, 1983)
SummaryThe object of this paper is to demonstrate the importance of state intervention on the national level in the development of world economy, and of the increasing extent to which the politics of the nation state are determined by the international division of labor. The author develops his analysis of the relationships between political power and world economy in three stages. After an update of the main transformations of world economy since the Second World War,and a rapid overview of the literature on the relationships of the state to world economy, he proposes his own reformulation of the problem around two main axes : on the one hand, political internalization, by which he means that state policies result from the coming together of internal factors (configurations of class struggles of the society in question) and external ones (contradiction of the international division of labor) ; and, on the other hand, the necessity of a theory of differentiation which can account for the place which each social formation and each state occupies in the world economy.